2019
DOI: 10.1002/jcp.29319
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the aberrant activation of Wnt/β‐catenin signaling by selenium supplementation ameliorates deoxynivalenol‐induced toxicity and catabolism in chondrocytes

Abstract: Kashin-Beck disease (KBD) is an endemic degenerative osteoarticular disorder associated with physical disability and a heavy economic burden. Contamination by mycotoxin deoxynivalenol (DON) and selenium deficiency have been proposed to be key etiological factors for KBD, and can work together to aggravate the progression of KBD.Nevertheless, the mechanism of DON in KBD remains elusive. In the present study, exposure to DON dose-dependently suppressed cell viability and expression of proproliferation marker PCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Both MMP1 and MMP14 are transmembrane MMPs that are critically involved in extracellular matrix proteolysis, cellular migration, and invasion. 36,37 They are two of the downstream molecules of Wnt/β-catenin signaling. 36,37 High expressions of tumor-derived MMP1 and MMP14 have been found to contribute to malignant and invasive tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MMP1 and MMP14 are transmembrane MMPs that are critically involved in extracellular matrix proteolysis, cellular migration, and invasion. 36,37 They are two of the downstream molecules of Wnt/β-catenin signaling. 36,37 High expressions of tumor-derived MMP1 and MMP14 have been found to contribute to malignant and invasive tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 They are two of the downstream molecules of Wnt/β-catenin signaling. 36,37 High expressions of tumor-derived MMP1 and MMP14 have been found to contribute to malignant and invasive tumor growth. [38][39][40][41][42] In addition, MMP1 and MMP14 were overexpressed in AB and associated with AB tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium supplementation reduces the activation of the DON-induced Wnt/β-catenin pathway and partially reverses cell damage. 73 Therefore, the precise relationship between DON and Wnt/β-catenin is yet to be determined. The effect of DON on the Wnt/β-catenin signaling pathway needs to be explored further.…”
Section: Signaling Involved In the Regulation Of Don-mediated Toxicitymentioning
confidence: 99%
“…71,72 Although most studies have shown that DON inhibits Wnt/ β-catenin signaling pathway activity to exert toxic effects, another study has reported that exposure to DON (0.4 μg/ mL) can promote the activation of the Wnt/β-catenin pathway. 73 DON can induce cell damage, inhibit matrix synthesis, activate Wnt/β-catenin signaling, and increase the catabolism of cells, promoting the development of the Kashin− Beck disease. Selenium supplementation reduces the activation of the DON-induced Wnt/β-catenin pathway and partially reverses cell damage.…”
Section: Signaling Involved In the Regulation Of Don-mediated Toxicitymentioning
confidence: 99%
“…These fungal secondary metabolites, which include ochratoxin A (OTA), deoxynivalenol (DON), fumonisin B (FBs), T-2 toxin, zearalenone (ZEA, ZEN), and aflatoxin B1 (AFB1), can contaminate grains anywhere between their growing period and their processing, with exposure to the mycotoxins resulting in acute and chronic poisoning in both animals and humans. In this context, studies have shown that selenium (Se), a microelement first discovered in 1817 (1), is effective at reducing the toxicity of mycotoxins (2)(3)(4). This element can exist as part of organic and inorganic compounds, with Se-methylselenocysteine (MSC), seleno-Lmethionine (SLM), and selenocysteine (5) representing the main organic types while selenades (e.g., H 2 Se, HSe − ), in contrast, selenates (e.g., SeO 2− 4 , HSeO − 4 , H 2 SeO 4 ) and selenites (e.g., SeO 2− 3 , HSeO − 3 , H 2 SeO 3 ) represent major inorganic ones (6).…”
Section: Introductionmentioning
confidence: 99%